Open-globe trauma epidemiology and clinical patterns at a level 1 trauma center - Su, Erin; Hwang, Jodi; Jiang, Xuejuan; Martinez-Camarillo, Juan Carlos (Digital Journal of Ophthalmology, 2024)
Introduction The purposes of this study were to evaluate demographics, prognostic factors, and clinical outcomes of open-globe injuries referred to a level 1 trauma center and to determine their associations with final visual acuity. Methods This was a retrospective review of all patients diagnosed with traumatic open globes at the LAC+USC Medical Center from August 2019 through August 2022. Demographic data and ocular trauma findings, including ocular trauma score (OTS) and visual acuity (VA), were collected. Associations between demographic data, ocular trauma details, and visual outcomes were assessed by the Fisher exact test and χ2 analyses. Results A total of 95 patients with traumatic open globes were included in the study (mean age ± SD, 42.7 ± 14.6 years). The majority were male (n = 87 [91.6%]) and Hispanic/Latino (n = 66 [69.5%]), with assault being the most likely cause of injury (n = 42 [44.2%]). Seventeen (17.9%) cases included periocular injuries, which significantly correlated with final visual acuities worse than 20/200 (P = 0.0084). OTS scores were found to be significantly associated with final visual acuities (P = 0.0006). No significant associations were found between long-standing ocular complications/sequelae (eg, traumatic cataracts, corneal scars, and choroidal effusion) and OTS score (df = 8, χ2 = 0.75) or visual acuity (df = 16, χ2 = 0.037). Conclusions This study demonstrates that OTS scores remain a valuable tool for final visual prognosis in ocular trauma patients. Significant periocular involvement in open-globe injuries may also play a role in predicting final visual prognosis.